What do we know about civil wars? - Mason, T. David (Thomas David) 1950-; Mitchell, Sara McLaughlin (Rowman & Littlefield, 2016)
In this timely book, leading scholars guide us through what the latest research tells us about the onset, duration, outcomes, and recurrence of civil wars, as well as the ongoing consequences of conflicts in war-torn countries such as Syria, Sudan, and Rwanda.